Functional metal-based 3D-printed electronics engineering: Tunability and bio-recognition. (August 2022) - Muñoz, Jose; Redondo, Edurne; Pumera, Martin
Highlights: 3D printed Cu electrode was decorated with Au and Ag. Chiral discrimination of amino acids was performed. Supramolecular determination of uranyl ions was carried out. Abstract: 3D-printing technology has brought light to the large-scale and sustainable production of a wide range of low-cost electronic devices with custom forms on-demand. Despite the current availability of mainstream carbon-based nanocomposite filaments, 3D-printing of noble metals is nowadays a challenge. Herein, a one-step functionalization approach has been devised for the straightforward and cost-effective manufacturing of functional metal-based 3D-printed electronics by galvanically replacing Cu-based 3D-printed (3D-Cu) electrodes with nobler metal counterparts, viz. Ag and Au. As a first demonstration of applicability, two appealing bio-electroanalytical approaches, such as the chiral discrimination of amino acids and the supramolecular determination of uranium have been considered —by taking advantage of the capability of noble metals to physically/chemically accommodate several molecular components—, reaching enhanced performances when compared with the pristine 3D-Cu counterpart. Consequently, this alchemy-inspired approach, which combines (i) 3D-Cu electrodes as sacrificial platforms with (ii) noble metals via a galvanic exchange reaction, provides a robust pathway to harbor molecular components in order to exploit metal-based 3D-printed electronics in real tasks. Graphical abstract: Image, graphical abstract